2004
DOI: 10.1111/j.1365-4632.2004.02536.x
|View full text |Cite
|
Sign up to set email alerts
|

“Hidradenitis suppurativa” is acne inversa! An appeal to (finally) abandon a misnomer

Abstract: The term "hidradenitis suppurativa" is firmly entrenched in the dermatological literature although it refers to a false pathogenetic concept. The term was historically coined based merely on the characteristic distribution of the apocrine glands and the anatomical coincidence with the disease process. At center stage is not a suppurative inflammation of the apocrine sweat glands but an occlusion of the hair follicles, comparable to acne vulgaris. Reviewing the literature on this subject, we were astonished to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 36 publications
5
102
0
7
Order By: Relevance
“…However, other studies found even higher rates of negative cultures [18,31]. In HS, fistulas may contain solely granulomatous inflammatory infiltrates with predominantly histiocytes and multinucleated giant cells, without significant bacterial growth [32,33]. Besides, due to the used culture conditions, distinct bacterial species may not grow.…”
Section: Discussionmentioning
confidence: 92%
“…However, other studies found even higher rates of negative cultures [18,31]. In HS, fistulas may contain solely granulomatous inflammatory infiltrates with predominantly histiocytes and multinucleated giant cells, without significant bacterial growth [32,33]. Besides, due to the used culture conditions, distinct bacterial species may not grow.…”
Section: Discussionmentioning
confidence: 92%
“…Erst mals be schrieb Vel peau im Jahr 1839 das Krank heits bild mit ent zünd li chen, ober fläch lich ab sze die ren den Ver än de rungen im Be reich der Axil len, der Brust und der Pe ria nal re gi on [24]. Auf grund der Schweiß drü sen ver tei lung und der ana tomi schen Nähe des Ent zün dungs pro zes ses zu die sen präg te zwi schen 1854 und 1865 der fran zö si sche Chi rurg Ver neuil den Begriff "hi dro sa dé ni te phleg mo neu se" [24].…”
Section: His To Ri Scher Ab Rissunclassified
“…Auf grund der Schweiß drü sen ver tei lung und der ana tomi schen Nähe des Ent zün dungs pro zes ses zu die sen präg te zwi schen 1854 und 1865 der fran zö si sche Chi rurg Ver neuil den Begriff "hi dro sa dé ni te phleg mo neu se" [24]. Nach dem Shel ley und Cahn 1955 in ei nem ok klu si ven Mo dell di la tier te, ent zün de te apo kri ne Drü sen gän ge nach wei sen konnten, pos tu lier ten sie, dass die "Hi dra de nitis sup pu ra ti va" eine bak te ri el le In fek ti on ver schlos se ner apo kri ner Drü sen sei [25].…”
Section: His To Ri Scher Ab Rissunclassified
“…Despite its historical name referring to sweat glands, it is a disease of the follicular apparatus, particularly of the areas where apocrine glands are present. Therefore, some authors called it acne inversa [1]. In analogy to acne, isotretinoin has been considered in the treatment of HS and has frequently been used in this context.…”
Section: Introductionmentioning
confidence: 99%